The Influence of Family Economic Conditions and Learning Interest on Mathematics Learning Achievement of Class IX Students of SMP Negeri 1 BandarTrading Academic Year 2022/2023 - Tanjung, Faya Rainvildasa; Sidabutar, Ropinus; Manurung, Suprapto (Lembaga Riset Mutiara Akbar, 2023)
The purpose of this study was to find out whether there was an effect of family economic conditions and interest in learning on the mathematics learning achievements of class IX students of SMP Negeri 1 BandarTrading T.A 2022/2023. This study uses a quantitative experimental research method. The population of this study were all students of class IX SMP Negeri 1 BandarTrading, totaling 184 students and a sample of 30 students, namely class IX-5. The instrument used was a questionnaire on the economic condition of the family as many as 20 items and a questionnaire on student interest in learning as many as 20 items. Based on data analysis of family economic conditions and students' learning interest on mathematics learning achievement, tcount > ttable (4.426 > 1.701) with a significant level of 0.05 so that H0 is rejected, Ha is accepted meaning that there is an influence of family economic conditions and students' learning interest on student mathematics learning achievement Class IX of SMP Negeri 1 Trade Dealer Academic Year 2022/2023